FAKTOR KUALITAS PELAYANAN DAN KEPERCAYAAN YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PADA TOKO ATK LISTRA ANUGERAH - Ayub Aruan Bone; Saiful; Leni Susilawati Anggraini (Tinta Nusantara 2018 Vol.1, 2020)
The purpose of this study was to determine the factors that influence the quality of service and trust in consumer purchasing decisions at the ATK Listra Anugerah Store. The analytical tools used by the author are Multiple Linear Regression Analysis, Validity and Reliability Test, and Hypothesis Testing. The results of the t-test on the service quality variable or X1 obtained a Sig probability of 0.001. Sig value <0.05 (0.001 <0.05), then the decision is H0 is rejected and Ha is accepted, which means that partially service quality has a significant effect on purchasing decisions. Meanwhile, the service quality variable or X1 has a t count of 3.627 with t table = 1.292. So t arithmetic > t table can be concluded that the variable X1 has a contribution to Y